CITY BRANDING AND DESTINATION BRANDING IN URBAN CULTURE VIEW - Amalia Herlina (Journal of Applied Management and Business, 2020)
This article discusses various aspects of city branding and destination branding activities that are reviewed in an urban culture perspective. This article is a series of opinions composed of a variety of literature reviews to support the development of the concepts of city branding and destination branding. This article also concludes that the new conditions have changed in the urban economy. The new picture has raised the urban recovery ventures in associations with regions and private associations. Urban industry was supplanted by administration segments like promoting, money and correspondence in this period.